1987
DOI: 10.1073/pnas.84.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative autoradiography of brain binding sites for the vesicular acetylcholine transport blocker 2-(4-phenylpiperidino)cyclohexanol (AH5183).

Abstract: ABSTRACT2-(4-Phenylpiperidino)cyclohexanol (AH-5183) is a noncompetitive and potent inhibitor of high-affinity acetylcholine transport into cholinergic vesicles. It is reported here that [3H]AH5183 binds specifically and saturably to slide-mounted sections of the rat forebrain (Kd = 1.1 to 2.2 x 10-8 M; Bm.. = 286 to 399 fmol/mg of protein). The association and dissociation rate constants for [3HJAH5183 binding are 8.6x 106 M-1*min-1 and 0.18 mini1, respectively. Bound[31H]AH5183 can be displaced by nonradioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…With the discovery of the anticholinergic properties of the lipophilic aminoalcohol (−)- trans -2-(4-phenylpiperidino)cyclohexanol (vesamicol, Figure 1), and the subsequent demonstration of a unique binding site for this molecule (the erstwhile vesamicol receptor) on cholinergic synaptic vesicles,1416 efforts were initiated to further characterize this site and to evaluate its potential utility as a cholinergic marker. In rat brain sections, the binding of [ 3 H]vesamicol was found to exhibit a regional heterogeneity which is correlated with ChAT activity and [ 3 H]hemicholinium-3 binding (an indicator of SDHAChT) 17,18. These results suggested that the vesamicol receptor may be a reliable cholinergic marker.…”
Section: Introductionmentioning
confidence: 90%
“…With the discovery of the anticholinergic properties of the lipophilic aminoalcohol (−)- trans -2-(4-phenylpiperidino)cyclohexanol (vesamicol, Figure 1), and the subsequent demonstration of a unique binding site for this molecule (the erstwhile vesamicol receptor) on cholinergic synaptic vesicles,1416 efforts were initiated to further characterize this site and to evaluate its potential utility as a cholinergic marker. In rat brain sections, the binding of [ 3 H]vesamicol was found to exhibit a regional heterogeneity which is correlated with ChAT activity and [ 3 H]hemicholinium-3 binding (an indicator of SDHAChT) 17,18. These results suggested that the vesamicol receptor may be a reliable cholinergic marker.…”
Section: Introductionmentioning
confidence: 90%
“…Because vesamicol was found to bind to VAChT in presynaptic cholinergic neurons with high affinity (Alter, 1988;Marien et al, 1987), many radiolabeled vesamicol analogs have been developed as radioligands for mapping presynaptic cholinergic neurons with SPECT (Efange et al, 1993;Jung et al, 1990;Shiba et al, 1995) and PET (Efange et al, 1999;Mulhollamd et al, 1998). Kawamura et al (2006) (Ishiwata et al, 2001) as a selective PET ligand for mapping the sigma-1 receptor in learning disability model monkeys produced by selectively destroying the p75NTR-positive cells in the right hemisphere of the brain affecting the cholinergic neuronal system using PET.…”
Section: Introductionmentioning
confidence: 99%
“…Cholinergic vesicle transport sites were labeled after incubation in 20 nM [3H]vesamicol for 60 minutes, followed by a 2 minute postwash (19,20). High affinity, sodium-dependent transmembrane choline uptake sites were labeled after incubation in 10 nM [3H]hemicholinium-3 for 120 minutes, followed by a 2 minute post-wash (21,22).…”
Section: Animals and Tissue Preparation Four Egyptian Tomb Bats (Roumentioning
confidence: 99%